Kualitas Spermatozoa dan Aktivitas Enzim Katalase dalam Darah Tikus Jantan Galur Sprague Dawley (SD) yang Diradiasi Sinar Ultraviolet - Panghiyangani, Roselina; Mashuri, . (Jurnal Kedokteran Indonesia, 2009)
Background: The damage of ozone layer in the atmosphere has reached to a serious extent, due to the increasing ultraviolet (UV) radiation, stemming from the green-house effect and the ozone hole. The increasing UV radiation is associated with the risk of some diseases or conditions, e.g. male infertility. The increasing UV radiation triggers the existence of reactive oxygen species (ROS)- free radicals that contain the oxygen atom â that are deemed to have an important role in male infertility. The excessive concentration of ROS causes oxidative stress as indicated by the activity of catalytic enzyme. This study aimed to examine the quality of spermatozoa and and the Activity of catalytic enzyme in the blood of male Sprague Dawley (SD) mice radiated by ultraviolet light of = 200-400 nm.Method: The study subjects were grouped into a group receiving UV radiation (P1) and a control group (Po). The UV radiation was carried out for 3 hours/ day for 60 days. The parameters for spermatozoa included motility perecentage, viability, while normality of the spermatozoa morphology was observed by microscope. The activity of catalytic enzyme in the blodd plasma was measured by spectrophotometry at = 240 nm.Results: The mean of catalytic enzyme for Po was: 75.2 Â± 6.9 % and P1: 47.1Â± 4.9%. The mean of spermatozoa motility percentage for Po was: 64.2Â± 11.3% and P1 : 0.7Â± 0.7%. The mean of spermatozoa viability percentage for Po was: 72.1 Â± 18.3% and P1: 28.4Â± 8.4%. The mean of normal spermatozoa morphology for Po was: 91.3Â±9.0% and P1: 95.2Â± 4.2%. All these differences were statistically significant.Conclusion: Ultra-violet radiation impairs the quality of spermatozoa and the activity of catalytic enzyme in the blood of male Sprague Dawley (sd) mice. Jurnal Kedokteran Indonesia: 1 (1): 4-7Keywords: ROS, catalytic enzyme, the quality of spermatozoa